MOTIVASI, GENDER, SELF EFFICACY DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA UNTUK MENGIKUTI UJIAN CPA TEST CENTER DI UNDIKNAS DENPASAR - Agung Omika Dewi (Universitas Pendidikan Nasional, 2020)
The purpose of this research is to determine the influence of career motivation, gender, self efficacy and job market considerations in the era of industrial revolution 4.0 on the interest of accounting students at Udiknas Denpasar to take the Certified Public Accountant (CPA) exam. This research use Theory of Planned Behavior that explain the relation between attitude and behavior. This study use primary data that are collected by questionnaire with incidental random sampling as the sampling technique. Data were analysed using multiple linear regression. The results are that career motivation, self efficacy and job market considerations in the industrial revolution era 4.0 had a significant effect on the interest of accounting students at Undiknas Denpasar to take the CPA exam. However, Gender did not significantly influence the interest of accounting students at Undiknas Denpasar to take the CPA exam.